A literature study on Methicillin-resistant Staphylococcus pseudintermedius (MRSP) : classification, resistance mechanisms, risk factors and clonal distribution - Fang, Yusi (SLU/Dept. of Biomedical Sciences and Veterinary Public Health (until 231231), 2015)
The increased frequency of reported Methicillin-resistant Staphylococcus pseudintermedius (MRSP) is of great concern to small animal healthcare due to limited options of antimicrobial therapy. The aim of this literature study is to investigate 1) characteristics and classification of S. pseudintermedius, 2) resistance mechanisms and emergence of MRSP, 3) risk factors for selection of MRSP, and 4) clonal distribution around the world. S. pseudintermedius is a skin and mucosal commensal in healthy dogs and cats, but can cause infections, including pyoderma. Beta-lactam antibiotics inhibit bacterial growth by binding to the penicillin binding protein (PBP), a vital enzyme in the synthesis of the bacterial cell wall. Methicillin-resistance in S. pseudintemedius is encoded by the mecA gene, that expresses modified PBP, named PBP2a or PBP2’, with a lower affinity for beta-lactams. The mecA gene is located on the staphylococcal chromosomal cassette, a mobile genetic element. In addition to beta-lactams, MRSP can be resistant to other classes of antibiotics drugs. The main risk factors for selection of MRSP are hospitalization, veterinary visits and former treatment with antibiotics. MRSP infection is therefore considered to be a nosocomial infection. The major clonal lineage predominant in Europe is ST71-J-t02-II–III; whilst in North America it is ST68-C-t06-V. Colonization of S. pseudintermedius in human is rare, and only one case of MRSP has been found up to date. Resistance genes are believed to be shared between species of staphylococci by horizontal gene transfer. However, more studies are needed to fully understand the mechanisms of horizontal gene transfer of the mecA gene.